If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 57 = 33 Reorder the terms: 57 + 2x = 33 Solving 57 + 2x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-57' to each side of the equation. 57 + -57 + 2x = 33 + -57 Combine like terms: 57 + -57 = 0 0 + 2x = 33 + -57 2x = 33 + -57 Combine like terms: 33 + -57 = -24 2x = -24 Divide each side by '2'. x = -12 Simplifying x = -12
| (x+2i)(x-2i)(x+4)=0 | | 6=J-5 | | 3y+7=2x-5 | | N/10-20=20 | | 100x-40y=320 | | 6x7/8= | | 3z+5z=0.6 | | (n)(n)+72=-17n | | 3x-5=6+x | | 6x+7=3(2x+4) | | (k)(k)-11k+30=0 | | (12y)(12y)+40y=7 | | 3x^2-8+5x=0 | | 3x+6=507 | | 10/3x1/2 | | 6d+4=-32 | | 5/6z=5/7 | | 18/sin40 | | a=bd | | p^2-14p=51 | | (d)(d)=5d | | 10c/2-32/4=56/8 | | (w)(w)=12 | | 3/7x1/7 | | 6-9(1-7n)=-21 | | -4x-16y=-12 | | 2y=-5x-3 | | (2x+8)+(3x-4)+x= | | 8(x+9)=72 | | 3y-10+y+y-10=180 | | (3b)(3b)+7b-6=0 | | x=(2x+8)+(3x-4)-x |